2012
DOI: 10.1111/j.1744-7402.2011.02749.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Ceramic Membranes (W‐Type Zeolite Membranes)

Abstract: In this article, effects of synthesis parameters (synthesis temperature, synthesis time, and number of layers) on W‐type zeolite membranes synthesized over flat SUS supports for O2/SF6 gas separation were experimentally investigated. Experiments were carried out at these levels of synthesis temperature: 165°C, 185°C, and 200°C; synthesis time: 6, 12, and 18 h and number of layers: 1 and 2. Permeation measurements, XRD and SEM analysis were used for characterization of the synthesized membranes. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…A suitable polymer material for nanofiltration membrane production is expected to resist thermal and chemical attack with outstanding mechanical strength and capacity to form flat-sheet or hollow fiber structure. Apart from the polymeric membranes, studies have also revealed the production of ceramic membranes from alumina, zirconia, silica and oxide mixture [81][82][83][84]. They are preferred to the polymeric membranes because of the existence of lower fouling, narrow pore size distribution, chemical stability and higher porosity in ceramic membranes.…”
Section: Nanofiltrationmentioning
confidence: 99%
“…A suitable polymer material for nanofiltration membrane production is expected to resist thermal and chemical attack with outstanding mechanical strength and capacity to form flat-sheet or hollow fiber structure. Apart from the polymeric membranes, studies have also revealed the production of ceramic membranes from alumina, zirconia, silica and oxide mixture [81][82][83][84]. They are preferred to the polymeric membranes because of the existence of lower fouling, narrow pore size distribution, chemical stability and higher porosity in ceramic membranes.…”
Section: Nanofiltrationmentioning
confidence: 99%
“…As crystal growth rate increased, larger crystals in size are formed and integrated faster as the membrane selective layer over the seeded support. Faster crystals integration is obtained in the compensate of lower average zeolite crystals density, i. e., more defective regions such as nonselective cracks or voids are appeared in the faster formed zeolitic membrane layer [40,49].…”
Section: The Synthesis Temperature Effect(s) On the Membranes Separatmentioning
confidence: 99%
“…The zeolite layer, which determines gas penetration behavior of the membrane, was formed properly at 12 h synthesis time and uniformly covered the support surface resulted in the reduced membrane gas penetration. Meanwhile there were still non zeolitic/amorphous regions kept the membrane's selectivity low [49]. At the synthesis time higher than 12 h, gaseous penetrants permeabilities increase due to increased porosity of the formed zeolite layer as the larger crystals are formed and the selective zeolite layer crystallinity and porosity enhance as well.…”
Section: The Synthesis Time Effect(s) On the Membranes Separation Permentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, materials used for ceramic membranes are zirconia, silica, alumina, mullite, oxide mixtures, and sintered metals (Harman, Koseoglu, Yigit, Beyhan, & Kitis, 2010;Hofs, Ogier, Vries, Beerendonk, & Cornelissen, 2011;Mohammadi & Maghsoodloorad, 2013;Pendergast & Hoek, 2011). Typical ceramic membranes are fabricated using the sol-gel process and are asymmetric in structure.…”
Section: Conventional Membrane Materialsmentioning
confidence: 99%